Feeding habits define habitat use by bats in an agricultural landscape of the Atlantic Forest - Rafael Souza Laurindo; Renan França Souza; Guilherme Oliveira Lemos; Naim Silva Teodoro; Leonardo Marin Bonilha; Fabiana Lucio Oliveira (Revista Mexicana de Biodiversidad)
Agricultural expansion and fragmentation of native habitats is considered to be the major cause of declining biodiversity worldwide, negatively impacting the provision and maintenance of nature’s contributions to people. Bats are a key group in agricultural landscapes, playing crucial ecological roles in pollination, seed dispersal and control of invertebrate populations. Due to interspecific differences in diet, morphology, physiology and behavior, bats differ in habitat use, with a species-specific response to landscape changes. In this study, we evaluated how bats from different trophic guilds relate to different habitats present in a hyperfragmented agricultural landscape. With the aid of mist nets, we captured 309 bats in 30 nights between June 2016 and July 2018. Our results show differences in habitat use between species of different trophic guilds. While insectivorous bats have a positive relationship with the amount of water present at the collection point, frugivorous bats show a negative response. These results reinforce the importance of landscape heterogeneity in agricultural mosaics for maintaining biodiversity.